A pilot study on LC–MS/MS quantification of remifentanil, etomidate, and rocuronium in maternal and fetal serum microsamples - Hao Liu; Meng Cai; Yong Peng; Jing-kun Miao; Jin Yu (Scientific Reports)
Abstract While remifentanil, etomidate, and rocuronium are increasingly used for cesarean section due to their favorable hemodynamic stability and fetal safety profile, their pharmacokinetics and potential effects on neonates remain poorly understood. This study developed and validated a rapid, sensitive LC–MS/MS method for simultaneous quantification of the three anesthetics in microsamples of 10 μl serum, followed by a paired maternal and umbilical cord serum investigation. After protein precipitation with acetonitrile, analytes were separated within 4 min using positive electrospray ionization in MRM mode. Method validation demonstrated excellent linearity (R2 > 0.99) for all compounds, with LLOQs of 0.15 ± 0.02 ng/mL (remifentanil), 16.87 ± 0.51 ng/mL (etomidate), and 106.73 ± 8.63 ng/mL (rocuronium). Precision (intra-/inter-day < 15%) and minimal carry-over (< 5%) met bioanalytical standards. Applied to 20 maternal-newborn pairs, the method quantified differential drug distribution: maternal arterial concentrations (remifentanil 4.75 ± 0.19 ng/mL; etomidate 412.71 ± 35.29 ng/mL; rocuronium 7.08 ± 0.48 μg/mL) exceeded umbilical vein levels (2.43 ± 0.13 ng/mL; 302.15 ± 29.03 ng/mL; 0.86 ± 0.16 μg/mL), which were higher than umbilical artery concentrations (1.33 ± 0.15 ng/mL; 166.24 ± 21.53 ng/mL; 0.44 ± 0.77 μg/mL). Calculated placental transfer rates significantly differed among anesthetics (remifentanil 0.52 ± 0.02; etomidate 0.75 ± 0.04; rocuronium 0.13 ± 0.02; all P < 0.001), reflecting distinct pharmacokinetic behaviors. The validated method enables reliable microvolume analysis for perinatal pharmacokinetic studies, particularly valuable when sample availability is limited. Its rapid throughput and sensitivity make it suitable for clinical research applications investigating maternal–fetal drug transfer dynamics.